2010
DOI: 10.1037/a0020512
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the co-morbidity between chronic pain and posttraumatic stress disorder on U.S. Veterans.

Abstract: The purpose of this study was to assess the comorbidity between chronic pain and posttraumatic stress disorder (PTSD) and examine the extent to which PTSD is associated with changes in the multidimensional experience of pain in a sample of Veterans with chronic pain. It was hypothesized that Veterans with comorbid chronic pain and PTSD would report significantly higher scores on measures of pain intensity, pain behaviors, pain-related disability, and affective distress than Veterans with pain alone. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 27 publications
3
60
1
Order By: Relevance
“…Previous literature has demonstrated associations between PTSD and intensified pain severity, disability, and interference [45][46][47]; however, at least one study did not corroborate this finding [4]. Results from the current study contribute further evidence to support the relationship between PTSD comorbidity and intensified pain features.…”
Section: Outcalt Et Al Veterans With Comorbid Chronic Pain and Ptsdsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous literature has demonstrated associations between PTSD and intensified pain severity, disability, and interference [45][46][47]; however, at least one study did not corroborate this finding [4]. Results from the current study contribute further evidence to support the relationship between PTSD comorbidity and intensified pain features.…”
Section: Outcalt Et Al Veterans With Comorbid Chronic Pain and Ptsdsupporting
confidence: 70%
“…Increasingly, the literature is illuminating more about the prevalence, costs, and impact of the comorbidity between these two conditions. In a recent study of Veterans receiving treatment for chronic pain, PTSD was identified in 49 percent of the sample [4]. Among Veterans seeking mental health treatment for PTSD, comorbid chronic pain was diagnosed in 66 percent of the patients studied [5].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review (Brennstuhl, Tarquinio, & Montel, 2015) included all studies on the relationship between chronic pain and PTSD in populations without any specific underlying somatic disorder and found 24 articles meeting the inclusion criteria. Of these articles, only one study (Otis et al, 2010) recruited participants from a pain management programme. These participants were all military veterans and the findings from this study might not be applicable to a civilian population.…”
Section: Introductionmentioning
confidence: 99%
“…diabetes) and osteoarthritis. 17 Conversely, Otis et al 18 studied 149 veterans in a psychology pain management programme. Diagnostic criteria for PTSD were met in 49% of cases using the PTSD Checklist -Military version (PCL-M).…”
Section: Pain and Comorbid Mental Health Problemsmentioning
confidence: 99%
“…Diagnostic criteria for PTSD were met in 49% of cases using the PTSD Checklist -Military version (PCL-M). 18 Two key theories have been proposed to account for the high comorbidity between PTSD and chronic pain. The 'shared vulnerability' hypothesis proposes that an underlying trait, such as anxiety sensitivity (the fear that anxiety symptoms are harmful) predisposes patients to both pain and PTSD.…”
Section: Pain and Comorbid Mental Health Problemsmentioning
confidence: 99%